Comparative Analysis of the Stability of the Russian and US Stock Markets in the Context of Geopolitical Transformations - E. V. Dorokhov (Мир новой экономики)
Subject. The global economic crisis of 2008, geopolitical crises between 2014 and 2023 and the socio-economic consequences of the COVID‑19 pandemic have a significant negative impact on the stock markets. The result of this influence is a significant increase in stock market volatility and instability.   The purpose of the article is to develop a methodology for assessing thesustainability of the stock market and, on its basis, carrying out a comparative analysis of the sustainability of the stock markets of the Russian Federation and the USA.   Methodology. Systematic and comparative analysis is used, as well as statistical methods and methods of the theory of cenoses.   Scientific novelty: a dimensionless indicator of the stability of the economic system of stock market companies has been developed.   Results. A methodology is proposed for assessing the sustainability of stock market issuing companies based on its model — economic cenosis. Within the framework of this methodology, a cenological analysis of structural changes and stability of the economic system under consideration is carried out. The developed methodology was tested based on the capitalization data of 100 companies listed on the Moscow Exchange and the S&P 500 index. A comparative analysis of the stability of the stock markets of the Russian Federation and the United States showed a sufficient degree of stability of the Russian stock market in relation to one of the most developed stock markets in the world — the US stock market.   Conclusions. The proposed methodology makes it possible to assess the sustainability of the stock market as a unified economic system of issuing companies based on their key parameter — capitalization. Maximizing the sustainability indicator makes it possible to determine the potential investment valuation of the selected company shares, provided that the economic system of the stock market, in the process of its evolution, strives for its most stable state.   Practical significance. The results and conclusions of the article may be in demand not only by regulatory organizations and stock market participants, but also by potential ordinary investors.